Transformasi Digital dalam Pendidikan dan Produktivitas Kerja Pendidik: Peran Artificial Intelligence sebagai Enabler Efisiensi Pedagogi - Debora Siahaan; Andressa Noviar Azhari; Dedi Sulistiyo Soegoto (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
Digital transformation in education has driven fundamental changes in pedagogical practices and educators' work patterns. The advancement of digital technology, particularly Artificial Intelligence (AI), enables automation, personalization, and data-driven decision-making within the learning process. This paper aims to comprehensively examine the relationship between the digital transformation of education, the utilization of Artificial Intelligence in pedagogy, and the work productivity of educators through a literature review method. The literature sources are drawn from reputable Indonesian journals published after 2019. The findings indicate that digital transformation serves as the foundation that enables AI adoption, while AI acts as an enabler of pedagogical efficiency by reducing the administrative burden on educators. Such efficiency has a positive impact on increasing educators' productivity. AI integration facilitates personalized teaching materials responsive to student needs, allowing educators to shift focus from routine tasks to more meaningful pedagogical interactions. This synergy not only optimizes workflows but also strengthens the strategic role of teachers in creating an inclusive, adaptive, and sustainable digital learning ecosystem for the future.This paper is expected to serve as a conceptual reference for the development of further research and education policies based on digital transformation and AI.